The impact of financial leverage on farms capacity to react in market shocks - Stefani, Gianluca; Gadanakis, Yiorgos; Lombardi, Ginevra Virginia; Tiberti, Marco (My University, 2017)
Evidence in the literature supports that farmers’ ability to choose the best available production technology is restricted when capital structure negatively influences farms’ financial performance. Therefore, empirical evidence is sought to provide an understanding of the relationship between capital structure and technical efficiency of Italian farms in a period of five years (2008 – 2013). It is concluded that significant improvements could be achieved for most of the farms in the sample by improving production and management practices. Furthermore, results provide an empirical support of the adjustment theory by showing a negative impact of debt to asset ratio to technical efficiency.
Keywords: Financial Leverage; Technical efficiency; Capital structure; Expenditure capacity; Italy